Seasonal water level fluctuations: Implications for reservoir limnology and management - Geraldes, Ana Maria (2008)
With the purpose of finding out whether seasonal water level fluctuations could affect water quality in a reservoir subjected to those changes, trends in environmental variables and in phytoplankton and zooplankton assemblages were analysed. The reservoir’s hydrological cycle was characterized by three regimes. The maximum level phase lasted from January to the beginning of June, the emptying phase existed between mid-June to the beginning of September and the minimum level phase lasted from mid-September to the beginning of the first autumn/winter rain events. The highest values of total phosphorus, soluble reactive phosphorus, nitrate, water colour and chlorophyll a were found during the minimum level phase. The phytoplankton assemblage was dominated by taxa typical of meso-eutrophic environments during the emptying and minimum level phases. However, during the maximum level phase, taxa generally found in more oligotrophic systems were observed here also. Similar to other disturbed systems, the zooplankton assemblage was dominated by Rotifera, except in summer and autumn when the cladoceran Ceriodaphnia quadrangula and/or the copepod Tropocyclops prasinus became dominant. Although those shifts seem to be related to water level variations, further research is needed to evaluate to what extent they might also be induced by other seasonal factors acting independently of water fluctuations. Based upon the obtained data, suggestions for reservoir management are proposed.